Alergia alimentaria a maní: conceptos clínicos, diagnósticos y terapéuticos - Peralta C., Teresa; Aguilera I., Raquel; Tordecilla F., Rocío; Guzmán M., María Antonieta; Ferrer C., Pablo (Revista Hospital Clínico Universidad de Chile, 2015)
The prevalence of food allergy (FA) is about 2-8%, with clinical manifestations ranging from localized symptoms, to severe anaphylactic reactions. FA is generally caused by milk, eggs, soybeans, tree nuts, peanuts, wheat, fish and crustacean; being peanut one of the main foods involved in Western countries. Although in other parts of the world peanut allergy (PA) is not a problem, probably due to timing of introduction into the diet, form and preparation, genetics, and the hygiene hypothesis. Unfortunately, in Chile there are no epidemiological data about FA or PA. A number of food allergens have been identified, which has improved patient diagnosis and treatment assessment. Regarding peanut, 9 allergens have been identified, Ara h 1 to Ara h 9 (Arachis hypogaea). The diagnosis of IgE-mediated PA is based on a consistent history and evidence of peanut-specific IgE sensitization, carried out by skin-prick testing or in vitro determination. PA treatment consists of peanuts avoidance, which often becomes difficult due to inadvertent consumption. Today promising treatments are under development, including oral induction tolerance or sublingual immunotherapy. These treatments offer the possibility of at least raising the threshold of the amount of peanut that would be necessary to cause a life-threatening allergic reaction.